Whatever happened to the British 'B' movie? Micro-budget film-making and the death of the one-hour supporting feature in the early 1960s. Issue 3 (3rd July 2017) - Mayne, Laura
Abstract : The British 'B' movie had its heyday from the post-war period up until the early 1960s. 'B' movies were cheap feature films of around one-hour long which were shown along with 'first' features as part of cinema double-bill programmes. But by 1963, British film companies had ceased production of second features for a number of reasons: they were no longer commercially viable due to rising production costs, their quality was much maligned at a time when American companies were producing higher budget, glossier fare, and by the early 1960s television was producing the kinds of low-budget crime dramas favoured by 'B' movie producers. However, the passing of the 'B' movie was mourned by some, who had seen it as a potential training ground for talent in an indigenous industry which offered few routes in for film-makers. Some cinema exhibitors also worried about how the decline of the 'B's would affect the staple cinema double bill. This article will examine the events which led to the decline of the British 'B' movie in the early 1960s, arguing that the demise of this production mode can shed light on the structure of the British film industry in the 1960s, as well as highlighting some of the challenges which faced film producers throughout the decade.